Reduced susceptibility of western corn rootworm (Diabrotica virgifera virgifera LeConte) populations to Cry34/35Ab1-expressing maize in northeast Nebraska - Jordan D. Reinders; Lance J. Meinke (Scientific Reports, 2022)
Abstract The western corn rootworm (WCR; Diabrotica virgifera virgifera LeConte) is a significant pest of maize (Zea mays L.) across the United States Corn Belt. Transgenic maize hybrids expressing insecticidal proteins derived from Bacillus thuringiensis (Bt) have been used to manage WCR since 2003. Widespread resistance to Cry3Bb1 (and associated cross-resistance to mCry3A and eCry3.1Ab) has placed increased selection pressure on Cry34/35Ab1 in single-protein and pyramided transgenic maize hybrids. Data on the susceptibility of Nebraska WCR populations to Cry34/35Ab1 has not been published since 2015 and plant-based bioassays conducted in 2017–2018 confirmed resistance to Cry3Bb1 + Cry34/35Ab1 maize, suggesting resistance to Cry34/35Ab1 has evolved in the Nebraska landscape. Therefore, plant-based bioassays were conducted on F1 progeny of WCR populations collected from northeast Nebraska in 2018 and 2019. Larval survival and development were used to classify resistance to Cry34/35Ab1 in each WCR population. Bioassays confirmed incomplete resistance to Cry34/35Ab1 maize in 21 of 30 WCR populations; 9 of 30 WCR populations remained susceptible to Cry34/35Ab1. Collectively, results indicate that northeast Nebraska WCR populations were in the initial stages of resistance evolution to Cry34/35Ab1 during 2018–2019. Appropriate resistance management strategies are needed to mitigate resistance and preserve efficacy of rootworm-active products containing Cry34/35Ab1.